The effect of the objectives in the major jurisprudential rules of the Malikis - Al-Azemi, Abdulrahman Mazyad Naser; Mansour, Mohamed Khaled Abdulaziz (Dirasat: Shari'a and Law Sciences, 2022)
Objectives :The study aims to show the impact of Shari'ah purposes on the objectives of the jurisprudential rules of Malikis, in terms of building these rules, forming them, expanding them, allocating their generality, restricting their absolute, and showing the impact of these purposes in taking into account the disagreement in the branches of these rules, and showing the impact of considering the history as one of the Shari'ah purposes in the actions of those charged with the major Fiqh rules. Methods: The study used the inductive approach to track the books of Makassed, origins, and fiqh rules of al-Maliki to extrapolate the scientific material and collect it. Then, the researcher used the analytical approach to analyze the scientific material and clarified its purpose. Moreover, the researcher used the deductive approach to deduce the impact of Makassed on jurisprudential rules of Malikisin in terms of origin, expansion, specialization, and restriction. Results: The Shari'ah purposes are the basis for the formation of the jurisprudential rules of the Malikis. The legitimate intentions influenced the jurisprudential rules of the Malikis in terms of capacity, narrowing, allocation, and restriction; all of this to bring interest or push a corrupter. Conclusions: Importance of directing the attention of researchers to the study of the relationship between the Shari'ah purposes and the Fiqh rules in general, and in the jurisprudential rules of the Malikis in particular, due to its benefits, while taking advantage of those benefits in adjusting the Fiqh developments.